Computer and information security - Coon, Audrey (Willford Press, 2016)
This comprehensive book provides a global overview of computer and information security. It offers an in-depth analysis of theories, technology and applications of this field. This book focuses on the emerging topic of security informatics. It brings forth some innovative research applications and rigorous case studies from around the globe under one umbrella. It includes contributions of renowned experts in the areas of cyber warfare and security, system security and data storage. This text will serve as a valuable reference to experts, IT engineers and interested readers.